Implementation of The Transfer of Home Ownership Credits Under The Law - Alfons, Maria (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This study investigates the role of banks in Indonesia's national growth, namely through the allocation of credit for home ownership financing. It delineates the legal frameworks regulating mortgage agreements, underscoring the responsibilities of borrowers and the banks' rights to enforce collateral in instances of default. The study examines complications stemming from the assignment of mortgage liabilities to third parties, emphasizing the difficulties of legal acknowledgment and safeguarding for new debtors when the initial borrower neglects to notify the bank of these transfers. The study investigates two main inquiries: the execution of debtor transfers in house ownership credit contracts, and the legal safeguards afforded to secondary creditors in cases of default by the principal debtor. The studies seek to elucidate the intricacies of mortgage agreements and strengthen legal protections for all parties involved